Conditional knockout of collecting duct bradykinin B2 receptors exacerbates angiotensin II-induced hypertension during high salt intake - Kopkan, Libor; Husková, Zuzana; Jíchová, Šárka; Červenková, Lenka; Červenka, Luděk; Saifudeen, Zubaida; El-Dahr, Samir S (Clinical and experimental hypertension (New York, N.Y., 2016)
We elucidated the role of collecting duct kinin B2 receptor (B2R) in the development of salt-sensitivity and angiotensin II (ANG II)-induced hypertension. To this end, we used a Cre-Lox recombination strategy to generate mice lacking Bdkrb2 gene for B2R in the collecting duct (Hoxb7-Cre(tg/+):Bdkrb2(flox/flox)). In 3 groups of control (Bdkrb2(flox/flox)) and 3 groups of UB(Bdkrb2-/-) mice, systolic blood pressure (SBP) responses to high salt intake (4 or 8% NaCl; HS) were monitored by radiotelemetry in comparison with standard salt diet (0.4% NaCl) prior to and during subcutaneous ANG II infusion (1000 ng/min/kg) via osmotic minipumps. High salt intakes alone for 2 weeks did not alter SBP in either strain. ANG II significantly increased SBP equally in control (121 ± 2 to 156 ± 3 mmHg) and UB(Bdkrb2-/-) mice (120 ± 2 to 153 ± 2 mmHg). The development of ANG II-induced hypertension was exacerbated by 4%HS in both control (125 ± 3 to 164 ± 5 mmHg) and UB(Bdkrb2-/-) mice (124 ± 2 to 162 ± 3 mmHg) during 2 weeks. Interestingly, 8%HS caused a more profound and earlier ANG II-induced hypertension in UB(Bdkrb2-/-) (129 ± 2 to 166 ± 3 mmHg) as compared to control (128 ± 2 to 158 ± 2 mmHg) and it was accompanied by body weight loss and increased mortality. In conclusion, targeted inactivation of B2R in the renal collecting duct does not cause salt-sensitivity; however, collecting duct B2R attenuates the hypertensive actions of ANG II under conditions of very high salt intake.
Keywords: Animals; hypertenze; Sodium Chloride, Dietary; angiotensin II; kuchyňská sůl; sběrací ledvinové kanálky; high salt diet; bradykinin receptor; receptor bradykininu B2; Mice; genový knockout; collecting duct; myši; krevní tlak; Receptor, Bradykinin B2; Hypertension; Male; Kidney Tubules, Collecting; modely nemocí na zvířatech; kallikrein–kinin system; Disease Models, Animal; hypertension; zvířata; mužské pohlaví; Cre recombinase; Blood Pressure; Gene Knockout Techniques; Angiotensin II